An evaluation of global LULC maps for the estimation of habitat use of a declining migratory waterbird along its flyway - van Toor, Mariëlle L.; Davranche, Aurélie; Delaunay, Gabriel; Murgue, Clément; Waldenström, Jonas; Arzel, Céline (ELSEVIER SCI LTD, 2025)
Global products of land use and land cover (LULC) provide maps with a consistent classification, thereby allowing for comparisons of resource and habitat use of species over large spatial scales. While global LULCs tend to be evaluated extensively, the distribution ranges of species can extend into remote areas that are hard to access for ground truthing. It is unclear how adequate global LULCs are for mapping habitat of long-distance migrants throughout their entire range. Here, we investigated whether different global LULCs could successfully capture the known preferences of a migratory wetland specialist, the Eurasian wigeon (Mareca penelope), along the East Atlantic flyway. We evaluated how well five different global LULC products captured known wigeon habitat preferences using remote tracking data, and tested whether a further classification based on wetland expert knowledge can improve on their performance. We found that average performance of global LULC products varied greatly, with ESA WorldCover performing best with a 94% correspondence to wigeon habitat. All products performed best in the Tundra biome, and worse in Boreal as well as Temperate forests. In the latter areas, our wetland expert LULC classification provided improved results by explicitly considering small and temporary wetlands, and wetlands underneath vegetation. Overall, habitat use of habitat specialists can inform us about habitat types that are currently not considered in large-scale LULC maps. We suggest LULC mapping methods integrate information from tracking of wetland specialists for a better detection of small and temporary wetlands on a global scale.